2012
DOI: 10.1175/mwr-d-11-00212.1
|View full text |Cite
|
Sign up to set email alerts
|

The HWRF Hurricane Ensemble Data Assimilation System (HEDAS) for High-Resolution Data: The Impact of Airborne Doppler Radar Observations in an OSSE

Abstract: Within the National Oceanic and Atmospheric Administration, the Hurricane Research Division of the Atlantic Oceanographic and Meteorological Laboratory has developed the Hurricane Weather Research and Forecasting (HWRF) Ensemble Data Assimilation System (HEDAS) to assimilate hurricane inner-core observations for high-resolution vortex initialization. HEDAS is based on a serial implementation of the square root ensemble Kalman filter. HWRF is configured with a horizontal grid spacing of 9/3 km on the outer/inne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 50 publications
4
39
0
Order By: Relevance
“…Recently, several studies have explored the use of ensemble-based DA methods to initialize hurricane forecasts and have shown great promise (e.g.. Torn and Hakim 2009;Zhang et al 2009a;Li and Liu 2009;Hamill et al 2011;Weng et al 2011;Zhang et al 2011;Aksoy et al 2012;Weng and Zhang 2012;Dong and Xue 2012). The key with ensemble-based DA is the use of an ensemble to estimate the forecast error statistics in a flow-dependent manner.…”
Section: Introdnctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have explored the use of ensemble-based DA methods to initialize hurricane forecasts and have shown great promise (e.g.. Torn and Hakim 2009;Zhang et al 2009a;Li and Liu 2009;Hamill et al 2011;Weng et al 2011;Zhang et al 2011;Aksoy et al 2012;Weng and Zhang 2012;Dong and Xue 2012). The key with ensemble-based DA is the use of an ensemble to estimate the forecast error statistics in a flow-dependent manner.…”
Section: Introdnctionmentioning
confidence: 99%
“…Recent studies have suggested that hybrid DA systems may represent the "best of both worlds" by combining the best aspects of the variational and EnKF systems (e.g., Buehner 2005;Wang et al 2007aWang et al , 2008aWang et al ,b, 2009Zhang et al 2009b;Buehner et al 2010a,b;Wang 2010). While preliminary tests of the hybrid DA system with real NWP models and data have shown great potential of the method for non-TC forecasts (e.g., Wang et al 2008b;Buehner et al 2010a,b) and for forecasts of TC tracks (e.g., Whitaker et al 2011), and there has been a growing body of literature documenting the success of using the EnKF to assimilate inner-core data for TC initialization at convection-allowing resolutions (e.g., Zhang et al 2009a;Weng et al 2011;Zhang et al 2011 ;Aksoy et al 2012;Weng and Zhang 2012;Dong and Xue 2012), to the authors' best knowledge, to date there is no published study applying a hybrid DA method to the assimilation of radar data at a convection-allowing resolution for TC predictions. This study serves as a pilot study applying the hybrid ensemble-threedimensional variational data assimilation (3DVAR) system developed for the Weather Research and Forecasting Model (WRF) (Wang et al 2008a) to explore its potential for assimilating radar observations for hurricane forecasts.…”
Section: Introdnctionmentioning
confidence: 99%
“…There have been successful and encouraging attempts to use ground-based and airborne Doppler radar data to initialize the inner cores of TCs. This has recently been described by Zhao and Jin (2008), Zhang et al (2009), Xiao et al (2009), Aksoy et al (2012), and Weng and Zhang (2012). Indeed, using a large sample of cases with airborne Doppler radar observations, Zhang et al (2011) clearly demonstrated the need for high-resolution inner-core observations for tropical cyclones from either in situ or remotely sensed observations.…”
Section: Introductionmentioning
confidence: 73%
“…( Aksoy et al 2012;Jung et al 2012). We examined the performance of the ensemble-based data assimilation and prediction system with Doppler radar observations systematically for all the 2008-2011 storms that had airborne Doppler missions.…”
Section: Resultsmentioning
confidence: 99%